2020
DOI: 10.7861/clinmed.2019-0457
|View full text |Cite
|
Sign up to set email alerts
|

Experience from the first UK inter-regional specialist multidisciplinary meeting in the diagnosis and management of IgG4-related disease

Abstract: Immunoglobulin G4-related disease (IgG4-RD) is a complex multisystem fibro-inflammatory disorder, requiring diagnostic differentiation from malignancy and other immunemediated conditions, and careful management to minimise glucocorticoid-induced toxicity and prevent progressive organ dysfunction. We describe the experience of the first inter-regional specialist IgG4-RD multidisciplinary team ABSTRACT meeting (MDM) incorporating a broad range of generalists and specialists, held 6-weekly via web-link between Ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 36 publications
(37 reference statements)
0
9
0
Order By: Relevance
“…The choice of outcomes were grouped into process indicators and outcome indicators. The process indicators included changes in diagnostic confirmation, 26 , 27 , 29 , 31 as well as therapeutic strategy and management. 26 , 27 , 29 , 30 All studies reporting process indicators demonstrated significant changes before and after the MDT ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The choice of outcomes were grouped into process indicators and outcome indicators. The process indicators included changes in diagnostic confirmation, 26 , 27 , 29 , 31 as well as therapeutic strategy and management. 26 , 27 , 29 , 30 All studies reporting process indicators demonstrated significant changes before and after the MDT ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The process indicators included changes in diagnostic confirmation, 26 , 27 , 29 , 31 as well as therapeutic strategy and management. 26 , 27 , 29 , 30 All studies reporting process indicators demonstrated significant changes before and after the MDT ( Table 1 ). The outcome indicators were composite measures of complications rates (e.g.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations